The Effects Of Augmented Reality Application On Learners’ Perception And Technology Acceptance In Physical Exercise - Ariffin, Ummie Haniffah (2024)
Augmented reality is an emerging technology that has rapidly evolved and developed. It was widely used in educational sectors as additional materials for school curricula. It also had been recently used in the health and sports fields. In this study, a marker-based AR application for physical exercise was developed. Its content was focused on four muscle-strengthening activities: push-ups, abdominal crunches, side planks, and step onto chair. This study intended to study the learners’ perception toward physical exercise application and their acceptance towards the AR apps for physical exercise.